THE CORRELATION BETWEEN NURSES' CAREER PATHS TO THE JOB SATISFACTION OF IMPLEMENTER NURSES IN THE WARD OF WANGAYA HOSPITAL - I Dewa Agung Gde Fanji Pradiptha,; Nyoman Putri Sriadi; I Dewa Ayu Marokta Utami Dewi; Ni Putu Maya Kartini Putri (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2020)
The greater the number of employees who work at a company will increase the problem possibility,the handling of these problems depends on management's awareness of the importance of humanresources in an organization. Human resources are the main resources in a company need a careerplanning and development. A good nurse career path enables to influence the improvement of worknurses satisfaction. This study aimed at analyzing the correlation between nurses' career paths to thejob satisfaction of implementer nurses in the Ward of Wangaya Hospital. This research usedcorrelation design research with cross sectional approach. The total sampling of the research were125 implementer nurses. The data analysis technique used was univariate analysis to explain ordescribe the characteristics of the research variables and the bivariate analysis used in this study isthe chi square test to analyze the correlation between nurses' career paths to the job satisfaction ofimplementer nurses in the Ward of Wangaya Hospital. The statistical test results obtained p value =0.001, this indicates that there was a correlation between career paths and job satisfaction ofimplementer nurses in the Ward of Wangaya Hospital. It is important for hospital to provideopportunities for implementer nurses to improve their career paths, one of which is through furthereducation, so that nurse job satisfaction can increase.